Exploring the predictors of foreign language anxiety: the roles of language proficiency, language exposure, and cognitive control - Xu, Yan; Xie, Zhilong (Frontiers in Psychiatry, 2024)
This research delves into unexplored territories of Foreign Language Anxiety (FLA), going beyond the traditional focus on language proficiency. We examined the nuanced roles of language exposure and individual differences in cognitive control abilities in shaping FLA. By engaging 46 English learners in a comprehensive assessment, our analysis uncovered significant yet distinct contributions of these factors to various aspects of FLA. Notably, proficiency predicted communication and overall anxiety, exposure influenced evaluation anxiety, while inhibition and mental set shifting abilities significantly predicted communication and test anxiety respectively. These findings illuminate the complexity of FLA, revealing that it stems from a multifaceted interplay of language proficiency, exposure, and cognitive control. This holistic understanding offers valuable insights for educators and learners alike, emphasizing the importance of tailored strategies that address not just language proficiency but also exposure opportunities and cognitive strengths.